2008
DOI: 10.1128/mcb.01108-07
|View full text |Cite
|
Sign up to set email alerts
|

MdmX Promotes Bipolar Mitosis To Suppress Transformation and Tumorigenesis in p53-Deficient Cells and Mice

Abstract: Mdm2 and MdmX are structurally related p53-binding proteins that function as critical negative regulators of p53 activity in embryonic and adult tissue. The overexpression of Mdm2 or MdmX inhibits p53 tumor suppressor functions in vitro, and the amplification of Mdm2 or MdmX is observed in human cancers retaining wild-type p53. We now demonstrate a surprising role for MdmX in suppressing tumorigenesis that is distinct from its oncogenic ability to inhibit p53. The deletion of MdmX induces multipolar mitotic sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
61
0

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(65 citation statements)
references
References 42 publications
4
61
0
Order By: Relevance
“…In this study, we proposed that a reason why a cancer cell would not retain the oncogenic activity of HDMX is because it has already inhibited p53 signaling by mutations of other key regulatory genes in the pathway and, therefore, the cell is no longer under selective pressure to sustain higher levels of HDMX. Furthermore, cells with deficient p53 activity could be under positive selection pressure to reduce HDMX levels as suggested by 2 recent studies, which report that full-length MDMX functions as a tumor suppressor in cells with deficient p53 function (41,42). Indeed, our observations made in 3 cell panels, comprising a total of 115 different cell lines, lend support to this model.…”
Section: Discussionsupporting
confidence: 71%
“…In this study, we proposed that a reason why a cancer cell would not retain the oncogenic activity of HDMX is because it has already inhibited p53 signaling by mutations of other key regulatory genes in the pathway and, therefore, the cell is no longer under selective pressure to sustain higher levels of HDMX. Furthermore, cells with deficient p53 activity could be under positive selection pressure to reduce HDMX levels as suggested by 2 recent studies, which report that full-length MDMX functions as a tumor suppressor in cells with deficient p53 function (41,42). Indeed, our observations made in 3 cell panels, comprising a total of 115 different cell lines, lend support to this model.…”
Section: Discussionsupporting
confidence: 71%
“…These effects appeared to be at least partially p53-independent. This study, together with previous reports, 25,26 suggests a role of MdmX that stretches beyond p53 inhibition.…”
Section: The P53 Pathway: From Normal To Tumor Cellsmentioning
confidence: 91%
“…An increasing body of evidence has shown that MDM4 also possesses p53-independent oncogenic functions (2,(18)(19)(20)(21). Since ASO-mediated exon 6 skipping directly affects MDM4 abundance, and not its ability to interact with p53, this approach is expected to also have an impact on the growth of MDM4-expressing, TP53-mutant melanoma cells.…”
Section: Mdm4 Is Unproductively Spliced In Most Normal Adult Tissues mentioning
confidence: 99%
“…Unfortunately, small molecules that selectively and efficiently disrupt the MDM4-p53 complexes have so far not been identified or introduced into the clinic. Moreover, an increasing body of evidence has shown that MDM4 possesses p53-independent oncogenic functions (2,(18)(19)(20)(21). Consistently, in addition to inducing p53-dependent apoptosis, MDM4 silencing in melanoma cells also caused cell-cycle arrest that could not be rescued upon concomitant inactivation of p53 (13).…”
Section: Introductionmentioning
confidence: 99%